Economical green low-carbon ultra-high performance concrete

By using alternative materials such as metakaolin, slag powder, machined sand, slurry gangue and servo fiber in ultra-high performance concrete, the problems of dependence and high carbon emissions of traditional ultra-high performance concrete materials are solved, and low-cost, low-carbon and environmentally friendly concrete production is achieved.

CN119912222AActive Publication Date: 2025-05-02SHANGHAI CONSTRUCTION GROUP CO LTD +1

Patent Information

Application Number
CN202510406999.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-05-02
Estimated Expiration
2045-04-02

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete has a dependence on material selection, resulting in high costs and high carbon emissions, and river sand mining leads to environmental protection problems.

Method used

Metakaolin and slag powder are used to replace silicate cement, machined sand and slurry gangue are used to replace river sand or quartz sand, servo fibers (made from paired cementing of bamboo fibers and PVA fibers) are used to replace steel fibers, and functional agents are used to stimulate the activity of the powder system.

Benefits of technology

It significantly reduces the cost of concrete production, reduces carbon dioxide emissions, improves the durability and toughness of concrete, and reduces dependence on natural resources, which has significant economic and low-carbon environmental significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to economical green low-carbon ultra-high performance concrete. The concrete is prepared from the following components in parts by mass (kg / m < 3 >): 450 to 550 parts of cement, 150 to 200 parts of metakaolin, 300 to 400 parts of granulated blast furnace slag powder, 350 to 450 parts of machine-made sand, 400 to 500 parts of powdery coal gangue, 78 to 156 parts of servo fiber, 13.5 to 20 parts of functional agent, 40 to 58.5 parts of composite admixture and 160 to 180 parts of water. The preparation method comprises the following steps: 1, adding the cement, the granulated blast-furnace slag powder and the powdery coal gangue into a stirrer, and stirring; 2, premixing and stirring the machine-made sand, 30% of a composite additive and 30% of water; 3, premixing and stirring the metakaolin, the functional agent and 30% of the composite additive; 4, uniformly mixing 40% of the composite admixture and 70% of water, and then slowly stirring; and 5, adding the servo fibers, and slowly stirring until the materials are uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to an economical green low-carbon ultra-high performance concrete. Background Art

[0002] As the urbanization process enters a new stage, people have higher and higher requirements for the quality of concrete structures that are closely related to their lives. Ultra-high performance concrete (UHPC) has the characteristics of ultra-high strength, high toughness, high workability and high durability. It has become a research hotspot in the field of concrete structure construction at home and abroad, and has been increasingly widely used in municipal administration, construction, urban renewal and other fields.

[0003] At present, ultra-high performance concrete mainly uses raw materials such as silicate cement, river sand or quartz sand, and steel fiber as core components to achieve the density of its system and thus meet the performance requirements of high strength, high toughness, and high durability. However, there are some problems in this type of mix design that cannot be ignored: (1) As a cementitious material, silicate cement will significantly increase carbon dioxide emissions if used in excessive amounts; (2) As a natural resource, river sand is currently difficult to control in the market due to over-exploitation, and its price is rising rapidly, and the environmental protection situation is becoming increasingly severe; (3) Although quartz sand has excellent quality, it is expensive, which will significantly increase the cost of concrete production and is not conducive to the market competition of concrete; (4) As the main toughening material, steel fiber has an important impact on the durability of concrete, but it has problems such as high price, difficulty in dispersion, easy exposure and rust, and heavy weight.

[0004] Therefore, how to provide an economical, green, low-carbon, ultra-high performance concrete is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] In view of the problem that traditional ultra-high performance concrete relies on materials such as silicate cement, river sand or quartz sand, and steel fiber, the present invention proposes an economical, green, and low-carbon ultra-high performance concrete, which partially replaces silicate cement with kaolin and slag powder, replaces natural river sand or quartz sand with machine-made sand and powdery coal gangue, replaces steel fiber with servo fiber based on bamboo fiber and PVA fiber, and uses functional agents to stimulate the activity of the powder system, thereby providing low-carbon, green cementitious materials, fine aggregates, and fiber materials, effectively overcoming the dependence of traditional ultra-high performance concrete on materials such as silicate cement, river sand or quartz sand, and steel fiber, reducing the cost of concrete production, and promoting the large-scale application of ultra-high performance concrete.

[0006] In order to solve the above technical problems, the present invention includes the following technical solutions: An economical green low-carbon ultra-high performance concrete, wherein the components of the concrete are in a mass ratio of (kg / m 3 ): Cement 450~550, metakaolin 150~200, granulated blast furnace slag powder 300~400, machine-made sand 350~450, powdery coal gangue 400~500, servo fiber 78~156, functional agent 13.5~20, composite admixture 40~58.5 and water 160~180.

[0007] Furthermore, the servo fiber is made of bamboo fiber and PVA fiber through a pairing bonding process.

[0008] Furthermore, the servo fiber manufacturing process comprises the following steps: The first step is the surface modification and reinforcement preparation process of bamboo fiber based on nano calcium carbonate: fresh bamboo is placed in a pressure tank, high-temperature saturated steam is introduced into the tank, and the temperature in the tank is pressurized to reach 160-180°C, and the temperature is kept for 40-60 minutes; the steam in the tank is discharged and the bamboo tube is taken out, and the bamboo tube is cut into bamboo pieces; the bamboo pieces are beaten with a bamboo hammer to obtain long-filament bamboo fiber; based on wet chemical deposition technology, a nano calcium carbonate in-situ modification process is used to accurately construct a nano-scale calcium carbonate reinforcement layer on the surface of the long-filament bamboo fiber; the long-filament bamboo fiber is cut into short-filament bamboo fiber with a length range of 15-25 mm; The second step is to paste it to the surface of short bamboo fiber to obtain servo fiber.

[0009] Furthermore, the PVA fiber has a length of 5-15 mm, a diameter of 18-22 μm, and a density of 1.0-1.5 g / cm 3 .

[0010] Furthermore, the functional agent is a mixed solution of sodium hydroxide and kiln dust in a mass ratio of 2:1, and the total mixing ratio is 9% to 10% of the mass of the metakaolin.

[0011] Furthermore, the composite admixture is a compound of a polycarboxylic acid-based high-efficiency water-reducing agent and a calcium sulphoaluminate-based expansion agent, and the total admixture ratio is 3.5% to 6.5% of the total amount of the cementitious material.

[0012] Furthermore, the cement is P.Ⅱ52.5 silicate cement, and the metakaolin is an ultrafine powder with a specific surface area of ​​26500m 2 / Kg, granulated blast furnace slag powder is S95 ore powder.

[0013] Furthermore, the machine-made sand and gravel powder content is ≤5%, the quartz content is ≥60%, and the powdery coal gangue is a high-strength lightweight aggregate of coal gangue.

[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides an economical green low-carbon ultra-high performance concrete, wherein the components of the concrete are in the following mass ratios (kg / m 3 ): cement 450~550, metakaolin 150~200, granulated blast furnace slag powder 300~400, machine-made sand 350~450, powdery coal gangue 400~500, servo fiber 78~156, functional agent 13.5~20, composite admixture 40~58.5 and water 160~180. The preparation method of the economical green low-carbon ultra-high performance concrete comprises: first, adding 100% cement, granulated blast furnace slag powder and powdery coal gangue into a mixer, and slowly stirring for 10 to 25 seconds until they are uniform; second, premixing 100% machine-made sand with 30% composite admixture and 30% water to obtain premixed machine-made sand, putting the premixed machine-made sand into the mixer, first slowly stirring for 10 to 25 seconds, and then quickly stirring for 8 to 10 seconds until they are uniform; third, premixing 100% metakaolin with 100% functional agent and 30% composite admixture to obtain premixed metakaolin. First, add the premixed kaolin into the mixer, stir slowly at 9-12 rpm for 10-25s, and then stir quickly at 12-24 rpm for 8-10s until uniform. Second, let it stand for 10-15s before starting slow stirring. Third, mix 40% of the composite admixture with 70% of the water, and then slowly and evenly add it into the mixer, stirring slowly for 45-60s until uniform. Fourth, add 100% of the servo fiber into the mixer slowly and evenly, stirring slowly for 60-120s until uniform, to obtain economical, green, low-carbon and ultra-high performance concrete.

[0015] Compared with the prior art, the beneficial effects of the present invention are mainly as follows: (1) The economical, green, low-carbon, ultra-high performance concrete provided by the present invention uses solid waste - metakaolin and slag powder to replace about 50% of the amount of silicate cement, which can significantly reduce the heat release of cement hydration, reduce the risk of concrete shrinkage and cracking, and improve the durability of concrete. At the same time, it can also greatly reduce the cost of concrete production and reduce carbon dioxide emissions, which has significant economic and low-carbon environmental protection significance.

[0016] (2) The economical, green, low-carbon, ultra-high performance concrete provided by the present invention uses machine-made sand as fine aggregate to replace part of the traditional river sand or quartz sand, which can significantly reduce the amount of river sand mining, save natural resources, protect the ecological environment, and reduce production costs; it uses powdery coal gangue to replace part of the traditional river sand or quartz sand, and utilizes its excellent filling efficiency, mechanical strength and certain volcanic ash activity to significantly improve the density of concrete, thereby effectively improving the mechanical and durability properties of concrete. At the same time, it can also realize the resource utilization of solid waste and reduce the cost of concrete production, which has significant social and economic benefits.

[0017] (3) The economical, green, low-carbon, ultra-high performance concrete provided by the present invention adopts servo fibers to replace traditional steel fibers. Through the surface modification and reinforcement preparation of bamboo fibers based on nano-calcium carbonate and the paired bonding process with PVA fibers, the respective performance advantages can be fully utilized, and the interface bonding strength between the servo fibers and the concrete matrix can be significantly improved, and the toughness and crack resistance of the concrete can be effectively enhanced. At the same time, the density of concrete can be effectively reduced to achieve a lightweight effect, and the production cost of concrete can be greatly reduced, effectively promoting the sustainable development of the traditional concrete industry towards greening and low carbonization.

[0018] (4) The economical green low-carbon ultra-high performance concrete provided by the present invention adopts a functional agent composed of a mixture of sodium hydroxide and kiln dust, which can effectively stimulate the activity of kaolin and powdery coal gangue, promote their hydration reaction process, and improve the density, mechanical and durability of concrete. DETAILED DESCRIPTION

[0019] The following is a further detailed description of an economical green low-carbon ultra-high performance concrete provided by the present invention in conjunction with specific embodiments. The advantages and features of the present invention will become more apparent from the following description.

[0020] The economical green low-carbon ultra-high performance concrete of the present invention is described below.

[0021] An economical green low-carbon ultra-high performance concrete, wherein the components of the concrete are in a mass ratio of (kg / m 3 ): Cement 450~550, metakaolin 150~200, granulated blast furnace slag powder 300~400, machine-made sand 350~450, powdery coal gangue 400~500, servo fiber 78~156, functional agent 13.5~20, composite admixture 40~58.5 and water 160~180.

[0022] More preferably, the servo fiber is made of bamboo fiber and PVA fiber through a pairing bonding process.

[0023] More preferably, the servo fiber manufacturing process comprises the following steps: The first step is the surface modification and reinforcement preparation process of bamboo fiber based on nano calcium carbonate: fresh bamboo is placed in a pressure tank, high-temperature saturated steam is introduced into the tank, and the temperature in the tank is pressurized to reach 160-180°C, and the temperature is kept for 40-60 minutes; the steam in the tank is discharged and the bamboo tube is taken out, and the bamboo tube is cut into bamboo pieces; the bamboo pieces are beaten with a bamboo hammer to obtain long-filament bamboo fiber; based on wet chemical deposition technology, a nano calcium carbonate in-situ modification process is used to accurately construct a nano-scale calcium carbonate reinforcement layer on the surface of the long-filament bamboo fiber; the long-filament bamboo fiber is cut into short-filament bamboo fiber with a length range of 15-25 mm; The second step is to paste it to the surface of short bamboo fiber to obtain servo fiber.

[0024] More preferably, the PVA fiber has a length of 5 to 15 mm, a diameter of 18 to 22 μm, and a density of 1.0 to 1.5 g / cm 3 .

[0025] More preferably, the functional agent is a mixed solution of sodium hydroxide and kiln dust in a mass ratio of 2:1, and the total mixing ratio is 9% to 10% of the mass of the metakaolin.

[0026] More preferably, the composite admixture is a compound of a polycarboxylic acid-based high-efficiency water-reducing agent and a calcium sulphoaluminate-type expansion agent, and the total admixture ratio is 3.5% to 6.5% of the total amount of the cementitious material.

[0027] More preferably, the cement is P.II52.5 silicate cement, and the metakaolin is an ultrafine powder with a specific surface area of ​​26500m 2 / Kg, granulated blast furnace slag powder is S95 ore powder.

[0028] More preferably, the content of machine-made sand and gravel powder is ≤5%, the content of quartz is ≥60%, and the powdery coal gangue is a high-strength lightweight aggregate of coal gangue.

[0029] The economical green low-carbon ultra-high performance concrete of the present invention is described in detail below with reference to specific embodiments.

[0030] Embodiment 1:

[0031] Tables 1 and 2 are the mix design and performance indicators of ordinary ultra-high performance concrete in Example 1; Tables 3 and 4 are the mix design and performance indicators of economical green low-carbon ultra-high performance concrete in Example 1.

[0032] Table 1 Mix ratio of ordinary ultra-high performance concrete (kg / m 3 )

[0033] Table 2 Performance indexes of ordinary ultra-high performance concrete

[0034] Table 3 Mix proportion of economical green low-carbon ultra-high performance concrete (kg / m 3 )

[0035] Table 4 Performance indexes of economical green low-carbon ultra-high performance concrete (kg / m 3 )

[0036] Embodiment 2:

[0037] Tables 5 and 6 are the mix design and performance indicators of ordinary ultra-high performance concrete in Example 2; Tables 7 and 8 are the mix design and performance indicators of economical green low-carbon ultra-high performance concrete in Example 2.

[0038] Table 5 Mix ratio of ordinary ultra-high performance concrete (kg / m 3 )

[0039] Table 6 Performance indexes of ordinary ultra-high performance concrete

[0040] Table 7 Economical green low-carbon ultra-high performance concrete mix proportion (kg / m 3 )

[0041] Table 8 Performance indicators of economical green low-carbon ultra-high performance concrete

[0042] It can be seen that compared with traditional ordinary ultra-high performance concrete, the economical green and low-carbon ultra-high performance concrete of the present invention, while greatly reducing the amount of cement and using servo fibers to replace traditional steel fibers / PVA fibers, not only effectively guarantees the basic mechanical properties of concrete (compressive and flexural strength), but also greatly improves the workability (expansion and expansion over time) and durability (anti-shrinkage performance) of concrete, while also significantly reducing the production cost of concrete and carbon dioxide emissions, and has significant economic and social benefits. Therefore, the economical green and low-carbon ultra-high performance concrete of the present invention has significant technological advancement and broad market prospects.

[0043] The above examples are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. The above embodiments only express several embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An economical green low-carbon ultra-high performance concrete, characterized in that: The mass ratio of each component of the concrete is (kg / m 3 ): Cement 450~550, metakaolin 150~200, granulated blast furnace slag powder 300~400, machine-made sand 350~450, powdery coal gangue 400~500, servo fiber 78~156, functional agent 13.5~20, composite admixture 40~58.5 and water 160~180.

2. The economical green low-carbon ultra-high performance concrete according to claim 1, characterized in that: The servo fiber is made of bamboo fiber and PVA fiber through a pairing bonding process.

3. The economical green low-carbon ultra-high performance concrete according to claim 2, characterized in that: The servo fiber manufacturing process comprises: The first step is the surface modification and reinforcement preparation process of bamboo fiber based on nano calcium carbonate: fresh bamboo is placed in a pressure tank, high-temperature saturated steam is introduced into the tank, and the temperature in the tank is pressurized to reach 160-180°C, and the temperature is kept for 40-60 minutes; the steam in the tank is discharged and the bamboo tube is taken out, and the bamboo tube is cut into bamboo pieces; the bamboo pieces are beaten with a bamboo hammer to obtain long-filament bamboo fiber; based on wet chemical deposition technology, a nano calcium carbonate in-situ modification process is used to accurately construct a nano-scale calcium carbonate reinforcement layer on the surface of the long-filament bamboo fiber; the long-filament bamboo fiber is cut into short-filament bamboo fiber with a length range of 15-25 mm; In the second step, an epoxy resin-based bonding process is used to pair the PVA fibers and bond them to the surface of short bamboo fibers in a mass ratio of 1:3 to 1:8 to obtain servo fibers.

4. The economical green low-carbon ultra-high performance concrete according to claim 3 is characterized in that: The PVA fiber has a length of 5-15 mm, a diameter of 18-22 μm, and a density of 1.0-1.5 g / cm 3 .

5. The economical green low-carbon ultra-high performance concrete according to claim 1, characterized in that: The functional agent is a mixed solution of sodium hydroxide and kiln dust in a mass ratio of 2:1, and the total mixing ratio is 9% to 10% of the mass of the metakaolin.

6. The economical green low-carbon ultra-high performance concrete according to claim 1, characterized in that: The composite admixture is prepared by compounding a polycarboxylic acid-based high-efficiency water reducing agent and a calcium sulphoaluminate-based expansion agent, and the total admixture ratio is 3.5% to 6.5% of the total amount of the cementitious material.

7. The economical green low-carbon ultra-high performance concrete according to claim 1, characterized in that: The cement is P.Ⅱ52.5 silicate cement, and the metakaolin is an ultrafine powder with a specific surface area of ​​26500m 2 / Kg, granulated blast furnace slag powder is S95 ore powder.

8. The economical green low-carbon ultra-high performance concrete according to claim 1, characterized in that: The machine-made sand and gravel powder has a content of ≤5% and a quartz content of ≥60%, and the powdery coal gangue is a high-strength lightweight aggregate of coal gangue.

Citation Information

Patent Citations

  • Ultrahigh-toughness alkali-activated shotcrete and preparation method thereof

    CN109503103A

  • Ultra-high performance concrete and preparation method thereof

    CN112430039A

  • Machine-made sand ultra-high performance concrete and preparation method thereof

    CN112777986A

  • Superfluid steam-curing-free ultra-high performance concrete and preparation method thereof

    CN113004001A

  • Low-energy-consumption ecological ultra-high-performance concrete and preparation method thereof

    CN114538843A

Cited By

  • Functional composite capsule servo fiber for concrete and preparation method

    CN120208573A